The Politic of Space in Martavan by Fahrul Khahim - Destriyadi (Abjad Journal of Humanities & Education, 2024)
The confinement and construction of Lita's body formed by the traditional environment forced her to fight against it all. In the short story Martavan by Fakhrul Khakim, Lita makes a solid attempt to redefine her body. By using Sara Upstone's theory of space politics, this paper tries to reveal how the efforts of space politics in this short story take place in the character. In this research, we explain the political classification of body space. This research uses a qualitative descriptive method. This research aims to reveal the failure of body politics in Fahrul Khakim's Martavan short story. The data collection techniques used are reading and note-taking techniques. The short story Martavan by Fahrul Khahim, seen from the perspective of postcolonialism, did not go smoothly and failed body politics. This phenomenon can be ascertained after chaos cannot be taken over by post-space. Resistance efforts in this short story can be done repeatedly to find a body upon which one agrees. This failure can be caused by the balance of resistance between East and West, where the East can only attack through the character Lita. Bapak and Hari are part of the West that can attack or indoctrinate the East. It is as if the women in this short story are unable to become their bodies to escape the boundaries that colonialism has created. The body present in the short story is a weakly constructed female body, failing to influence or dismantle the construction of the body.